2010
DOI: 10.1152/ajpheart.00065.2010
|View full text |Cite
|
Sign up to set email alerts
|

Short-term disruption in regional left ventricular electrical conduction patterns increases interstitial matrix metalloproteinase activity

Abstract: Increased matrix metalloproteinase (MMP) abundance occurs with adverse left ventricular (LV) remodeling in a number of cardiac disease states, including those induced by long-standing arrhythmias. However, whether regionally contained aberrant electrical activation of the LV, with consequent dyskinesia, alters interstitial MMP activation remained unknown. Electrical activation of the LV of pigs (n ϭ 10, 30 -35 kg) was achieved by pacing (150 beats/min) at left atrial and LV sites such that normal atrioventricu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Alternatively, the use of a greater electrical current during suprathreshold stimulation may also be sufficient to trigger the degranulation of neutrophils. This hypothesis is supported by the results of Mukherjee et al (12), where 60 min of LV pacing in the presence of dyskinesis was sufficient to trigger MMP activation and collagen degradation.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Alternatively, the use of a greater electrical current during suprathreshold stimulation may also be sufficient to trigger the degranulation of neutrophils. This hypothesis is supported by the results of Mukherjee et al (12), where 60 min of LV pacing in the presence of dyskinesis was sufficient to trigger MMP activation and collagen degradation.…”
Section: Discussionsupporting
confidence: 60%
“…The differences likely arise from variations used in the implementation of the zymography technique and the large number of samples examined. A recent study (12) reported on increases in Values are means Ϯ SE; n ϭ 9 for the nonpaced group, 5 for the subthreshold group, and 9 for the suprathreshold group. HR, heart rate; LVSP, left ventricular (LV) systolic pressure; LVEDP, LV end-diastolic pressure; ϩdP/dt, increase of LV pressure; ϪdP/dt, decrease of LV pressure; N/A, not applicable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some in vitro models have shown that fibroblasts grown on mechanically relaxed collagen I produced high levels of MMP-2 and MT1-MMP 26 , while others have shown that cyclic stretching of myofibroblasts causes increased MT-MMP activity 27 . Altering the mechanical activation pattern of a region of the LV free wall in vivo increased MMP-9 levels, interstitial MMP activity, and increased collagen degradation 19, 28 . Rohde et.…”
Section: Discussionmentioning
confidence: 99%
“…A specific global MMP fluorogenic substrate (Enzo Life Sciences BML-P126; excitation 330 nm; emission 405 nm) was utilized to measure MMP activity within the tissue homogenates 19, 20 . Briefly, 30 μM of the fluorogenic MMP substrate was incubated with myocardial tissue extract (25 μg) and fluorescence of the cleaved substrate recorded (FLUOstar, BMG Labtech, Durham, NC).…”
Section: Methodsmentioning
confidence: 99%